Dielectric composition and multilayer ceramic electronic component

The introduction of a dielectric composition with specific segregations in the perovskite-type compound addresses the durability issues of laminated ceramic electronic components, enhancing their resistance to cracking in harsh environments while maintaining high relative permittivity.

JP7653303B2Active Publication Date: 2025-03-28TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021088541
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-26
Publication Date
2025-03-28
Estimated Expiration
2041-05-26

AI Technical Summary

Technical Problem

Laminated ceramic electronic components face durability issues due to structural defects like cracks, which are exacerbated by differences in properties between ceramic and internal electrode layers, particularly in high temperature and high humidity environments.

Method used

A dielectric composition is developed that includes a perovskite-type compound with a first segregation containing Ba, P, and O, where the Ba/Ti molar ratio is 1.20 or more, and optionally a second segregation with Si, rare earth elements, and O, to enhance durability and relative permittivity.

Benefits of technology

The dielectric composition and resulting laminated ceramic electronic components exhibit improved durability and resistance to cracking in high temperature and high humidity environments, while maintaining high relative permittivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653303000005
    Figure 0007653303000005
  • Figure 0007653303000006
    Figure 0007653303000006
  • Figure 0007653303000001
    Figure 0007653303000001
Patent Text Reader

Abstract

To provide a dielectric composition with excellent durability against high temperature and high humidity environments and a laminated ceramic electronic component.SOLUTION: A dielectric composition has dielectric particles containing as a major component a perovskite-type compound represented by ABO3 and a first segregation including at least Ba, P, and O. Furthermore, the molar ratio of Ba to Ti (Ba / Ti) in the first segregation is 1.20 or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dielectric composition and a multilayer ceramic electronic component including the dielectric composition. [Background technology]

[0002] As shown in Patent Document 1, a multilayer ceramic electronic component is known in which ceramic layers made of a dielectric composition and internal electrode layers are alternately laminated. In this multilayer ceramic electronic component, there is a difference in properties such as the shrinkage rate and the linear expansion coefficient between the ceramic layers and the internal electrode layers. Due to this difference in properties, the ceramic layers made of the dielectric composition are prone to structural defects such as cracks, and durability in high-temperature and high-humidity environments may decrease. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-012418 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a dielectric composition and a multilayer ceramic electronic component that are excellent in durability in high-temperature and high-humidity environments. [Means for solving the problem]

[0005] In order to achieve the above object, the dielectric composition according to the present invention comprises: Dielectric particles containing a perovskite compound represented by ABO3 as a main component; A first segregation containing at least Ba, P, and O; The molar ratio of Ba to Ti (Ba / Ti) in the first segregation is 1.20 or more.

[0006] The dielectric composition of the present invention has the first segregation containing the predetermined components as described above, and it is believed that the first segregation can suppress the occurrence of cracks. As a result, the dielectric composition of the present invention and the multilayer ceramic electronic component containing the dielectric composition exhibit excellent durability in high-temperature and high-humidity environments.

[0007] Preferably, the content ratio of the first segregation is 0.007 pieces / μm 2 More than 0.4 pieces / μm 2 The following is the result.

[0008] Preferably, the molar ratio of P to Si (P / Si) in the first segregation is 2.5 or more.

[0009] Preferably, the average grain size of the first segregation is 0.05 μm or more and 0.50 μm or less.

[0010] Preferably, the dielectric composition of the present invention further has a second segregation containing at least Si, a rare earth element R, and O. In this case, the rare earth element R is preferably Y and / or Dy. Furthermore, the content ratio of the first segregation is set to N1 (unit: number / μm 2 ), and the content ratio of the second segregation is N2 (unit: number / μm 2 ), it is preferable that N2 / N1 is 0.5 or more and 10 or less.

[0011] Preferably, the perovskite compound is barium titanate. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of a multilayer ceramic capacitor according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of the ceramic layer 10 shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this embodiment, a multilayer ceramic capacitor 2 shown in Fig. 1 will be described as an example of a ceramic electronic component according to the present invention. The multilayer ceramic capacitor 2 has an element body 4 and a pair of external electrodes 6 formed on the outer surface of the element body 4.

[0014] The shape of the element body 4 shown in FIG. 1 is generally a substantially rectangular parallelepiped shape, and has two end faces 4a facing each other in the X-axis direction, two side faces 4b facing each other in the Y-axis direction, and two side faces 4b facing each other in the Z-axis direction. However, the shape of the element body 4 is not particularly limited, and may be an elliptical cylinder, a cylindrical shape, or another prismatic shape. In addition, the outer dimensions of the element body 4 are also not particularly limited, and may be, for example, a length L0 in the X-axis direction of 0.4 mm to 5.7 mm, a width W0 in the Y-axis direction of 0.2 mm to 5.0 mm, and a height T0 in the Z-axis direction of 0.2 mm to 3.0 mm. In this embodiment, the X-axis, Y-axis, and Z-axis are perpendicular to each other.

[0015] The element body 4 has ceramic layers 10 and internal electrode layers 12 that are substantially parallel to a plane including the X-axis and Y-axis, and inside the element body 4, the ceramic layers 10 and the internal electrode layers 12 are alternately stacked along the Z-axis direction. Here, "substantially parallel" means that most parts are parallel, but may have some parts that are not parallel, and the ceramic layers 10 and the internal electrode layers 12 may have some unevenness or be inclined.

[0016] The ceramic layers 10 are made of a dielectric composition described later. The average thickness (interlayer thickness) of each ceramic layer 10 is not particularly limited, and may be, for example, 100 μm or less, and preferably 30 μm or less. The number of layers of the ceramic layers 10 may be determined according to the desired characteristics, and is not particularly limited. For example, it may be 20 layers or more, and more preferably 50 layers or more.

[0017] Meanwhile, the internal electrode layers 12 are laminated between the ceramic layers 10, and the number of layers is determined according to the number of layers of the ceramic layers 10. The average thickness of each of the internal electrode layers 12 is not particularly limited, and can be, for example, 3.0 μm or less. The average thickness of the ceramic layers 10 and the average thickness of the internal electrode layers 12 may be calculated by observing a cross section as shown in FIG. 1 using a metallurgical microscope and measuring the thickness of each layer (10, 12) at at least five points.

[0018] The internal electrode layers 12 are laminated such that one end is alternately exposed on two end faces 4a facing each other in the X-axis direction of the element body 4. A pair of external electrodes 6 are formed on one end face 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. By forming the internal electrode layers 12 and external electrodes 6 in this manner, a capacitor circuit is formed by the external electrodes 6 and the internal electrode layers 12. That is, the ceramic layers 10 present in the capacitance region are sandwiched between the internal electrode layers 12 of different polarities, and a voltage can be applied to the ceramic layers 10.

[0019] The internal electrode layer 12 is made of a conductive material and preferably contains Ni as a main component. Specifically, the conductive material of the internal electrode layer 12 is preferably pure Ni or a Ni-based alloy containing 85 wt% or more of Ni, and the Ni-based alloy may contain one or more elements selected from Mn, Cu, Cr, etc. In addition to the above-mentioned conductive material, the internal electrode layer 12 may contain particles of a perovskite compound having a composition similar to that of the main component of the ceramic layer 10 as a common material. Furthermore, the internal electrode layer 12 may contain a small amount (for example, about 0.1 mass% or less) of non-metallic components such as S and P, and may contain voids. Note that when the common material or voids are contained in the internal electrode layer 12, discontinuous parts where no electrodes (conductive materials) exist may be formed in the internal electrode layer 12.

[0020] The pair of external electrodes 6 may include a baked electrode layer, a resin electrode layer, a plated electrode layer, etc., and may be composed of a single electrode layer or may be composed of a laminate of multiple electrode layers. For example, the external electrodes 6 may have a three-layer structure of a baked electrode layer-a Ni plating layer-a Sn plating layer (laminate in the order listed), in which case the Sn plating layer is located on the outermost surface of the external electrodes 6, and therefore the solder wettability of the external electrodes 6 is good.

[0021] 1, the external electrode 6 integrally has an end surface portion formed on the end surface 4a in the X-axis direction of the element body 4, and extension portions formed at the ends in the X-axis direction on the four side surfaces 4b of the element body 4. That is, the pair of external electrodes 6 are each formed so as to wrap around from the end surface 4a to the side surfaces 4b of the element body 4, and are insulated so as not to contact each other in the X-axis direction.

[0022] The extensions of the external electrodes 6 are not essential, and the external electrodes 6 may be composed of only the end surface portions. Alternatively, when the multilayer ceramic capacitor 2 is surface-mounted on a substrate, the extensions of the external electrodes 6 need only be formed on at least the side surface 4b facing the mounting surface of the substrate, and do not necessarily have to be formed on the side surface 4b opposite the mounting surface.

[0023] Next, the dielectric composition of the ceramic layer 10 will be described in detail.

[0024] The dielectric composition of the ceramic layer 10 contains a perovskite type compound represented by the general formula ABO3 as a main component. Here, the main component of the ceramic layer 10 (main component of the dielectric composition) means a component that occupies 80 mol % or more of the ceramic layer 10. In this embodiment, the perovskite type compound as the main component is preferably barium titanate (BT), and this barium titanate has the composition formula (Ba 1-a-b Sr a Ca b ) m (Ti 1-c-d Zr c Hf d )O3.

[0025] In the above composition formula, the symbols a, b, c, d, and m each indicate an element ratio, and each element ratio is not particularly limited and can be set to a known range. For example, m indicates the element ratio of the A site to the B site, and can generally be in the range of 1.0 to 1.1. Furthermore, a indicates the element ratio of Sr in the A site, and b indicates the element ratio of Ca in the A site. In this embodiment, it is preferable that 0≦a+b≦0.1. Furthermore, c indicates the element ratio of Zr in the B site, and d indicates the element ratio of Hf in the B site. In this embodiment, it is preferable that 0≦c+d≦0.15. The element ratio of oxygen (O) in the above composition formula may be slightly deviated from the stoichiometric composition.

[0026] In addition to the above-mentioned main components, the ceramic layer 10 may contain auxiliary components. Examples of the auxiliary components include Mn compounds, Mg compounds, Cr compounds, Ni compounds, rare earth element compounds, Si compounds, Li compounds, B compounds, V compounds, Al compounds, Ca compounds, and Zr compounds, and the types and combinations of the auxiliary components and the amounts added are not particularly limited.

[0027] The component compositions of the ceramic layers 10 and the internal electrode layers 12 may be analyzed by inductively coupled plasma optical emission spectroscopy (ICP), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray fluorescence spectrometry (XRF), energy dispersive X-ray spectrometry (EDX), or an electron probe microanalyzer (EPMA) equipped with a wavelength dispersive X-ray spectrometer (WDS).

[0028] The ceramic layer 10 containing the above components has an internal structure as shown in FIG. 2, and the ceramic layer 10 includes dielectric particles 20 as a parent phase, segregation phases (21, 22) having predetermined characteristics, and grain boundaries 23 located between the dielectric particles 20.

[0029] The dielectric particles 20 are composed of the main component (perovskite type compound) of the ceramic layer 10 described above. When the ceramic layer 10 contains an auxiliary component, the dielectric particles 20 may have the auxiliary component dissolved therein in addition to the main component. The dielectric particles 20 may have a core-shell structure due to the auxiliary component being dissolved therein. The average particle size of the dielectric particles 20 may be 2.0 μm or less, and is preferably 0.1 μm to 1.0 μm.

[0030] The average particle size of the dielectric particles 20 can be measured by observing a cross section of the ceramic layer 10 as shown in Fig. 2 using a scanning electron microscope (SEM) or a scanning transmission electron microscope (STEM) and performing image analysis on the obtained cross section photograph. For example, the average particle size of the dielectric particles 20 may be calculated by measuring the circle equivalent diameters of at least 100 or more dielectric particles 20.

[0031] The ceramic layer 10 of this embodiment includes a first segregation 21 as shown in Fig. 2. The first segregation 21 is a composite oxide phase having a higher P concentration than the dielectric particles 20, and includes at least P (phosphorus), Ba, and O (oxygen). In addition to the above elements, the first segregation 21 may include constituent elements of the ceramic layer 10 (elements such as Sr, Ca, Ti, Zr, and Hf that may be included in the main component, and subcomponent elements). When the total content of elements excluding oxygen included in the first segregation 21 is 100 mol, the content of P in the first segregation 21 is preferably 1 mol% or more, and more preferably 3 mol% to 40 mol%.

[0032] Moreover, the first segregation 21 has a predetermined element ratio. Specifically, in the first segregation 21, the molar ratio of Ba to Ti (hereinafter referred to as Ba / Ti ratio) is higher than that in the dielectric particle 20, and is 1.20 or more. In this way, when the Ba / Ti ratio in the first segregation 21 is higher than that in the dielectric particle 20, it can be determined that Ba is present in the first segregation 21. Note that the upper limit of the Ba / Ti ratio in the first segregation 21 is not particularly limited, and the first segregation 21 does not need to contain Ti. In the multilayer ceramic capacitor 2 of this embodiment, the presence of a segregation phase (first segregation 21) of Ba and P in the ceramic layer 10 exhibits excellent corrosion resistance in a high-temperature and high-humidity environment.

[0033] In addition, as described above, the ceramic layer 10 may contain a Si compound as an auxiliary component, and the Si added as an auxiliary component may be contained in the first segregation 21. However, the Si content in the first segregation 21 is preferably lower than the P content, and the molar ratio of P to Si in the first segregation 21 (hereinafter referred to as the P / Si ratio) is preferably 2.5 or more, and more preferably 3.0 or more. When the P / Si ratio satisfies the above requirements, durability against high temperature and high humidity environments is further improved. Note that the first segregation 21 does not need to contain Si, and the upper limit of the P / Si ratio is not particularly limited.

[0034] Although the detailed composition of the first segregation 21 is not particularly limited, the crystal system of the first segregation 21 is preferably a trigonal system. An example of a trigonal complex oxide is Ba3(PO4)2. When the first segregation 21 is a trigonal complex oxide as described above, durability against a high-temperature and high-humidity environment can be further improved.

[0035] In this embodiment, it is preferable to identify the first segregation 21 by using a combination of mapping analysis and point analysis by EDX or WDS. For example, a mapping analysis is performed on a cross section of the ceramic layer 10 as shown in FIG. 2, and the location where P is segregated is identified from the obtained mapping image of P. Here, the "location where P is segregated" means a region where the P concentration is higher than that of the dielectric particles 20, and can be visually identified from the mapping image of P. Then, a point analysis is performed on the region where P is segregated, and the Ba / Ti ratio in the segregation region is measured. If the Ba / Ti ratio is 1.20 or more, it is determined that the measured P segregation region is the first segregation 21. Measurement conditions such as the measurement field of view and resolution in the mapping analysis and point analysis are not particularly limited as long as they are appropriately set to conditions that allow analysis of segregation.

[0036] The average grain size of the first segregations 21 can be 1.0 μm or less, and is preferably in the range of 0.05 μm or more and 0.50 μm or less. The average grain size of the first segregations 21 may be calculated by identifying at least five or more first segregations 21 by EDX or WDS, and then measuring the circle equivalent diameter of the identified segregations 22 by image analysis.

[0037] In the present embodiment, the content ratio of the first segregations 21 in the ceramic layer 10 is expressed as the number N1 (unit: number / μm 2 ) This number N1 is defined as 0.005 pieces / μm 2 ~0.5 pieces / μm 2 can be in the range of 0.007 pieces / μm 2 In addition, when the influence of the first segregation 21 on the relative dielectric constant is taken into consideration, the number N1 is preferably 0.4 pieces / μm 2 In this way, it is preferable that the number N1 is 0.007 to 0.4 pieces / μm 2 By setting the value within this range, it is possible to achieve both improved durability in a high temperature and high humidity environment and a high relative dielectric constant.

[0038] The number N1 is determined by observing a cross section of the ceramic layer 10 as shown in FIG. 2 in multiple fields of view using a SEM or STEM, and determining that the number of defects is at least 1000 μm in total. 2 This can be calculated by counting the number of first segregations 21 present in the above cross section.

[0039] In the ceramic layer 10 of this embodiment, in addition to the first segregation 21, a second segregation 22 having a predetermined characteristic is preferably present. This second segregation 22 is a composite oxide phase containing at least Si, a rare earth element R, and O, and the total content of Si and the rare earth element R in the second segregation 22 is higher than that in the dielectric particles 20. The rare earth element R contained in the second segregation 22 is preferably Y (yttrium) and / or Dy (dysprosium). The presence of this R-Si-O based second segregation 22 in the ceramic layer 10 increases the sintering density of the ceramic layer 10, and further improves the durability against high temperature and high humidity environments.

[0040] In addition to the above elements, the second segregation 22 may contain constituent elements of the ceramic layer 10, and in particular, Ba is preferably contained. When the second segregation 22 contains Ba, the Ba / Ti ratio in the second segregation 22 is preferably higher than the Ba / Ti ratio in the dielectric particles 20, and more preferably 1.20 or more. The detailed composition of the second segregation 22 is not particularly limited, and may be, for example, Ba5Dy of the tetragonal system. 13 SiO 41 By including Ba in the second segregation 22, the bonding strength between the dielectric particles 20 can be increased, and durability in a high-temperature and high-humidity environment can be further improved.

[0041] The second segregation 22 can be identified by mapping analysis using EDX or WDS. In this case, the mapping analysis may be performed in the same manner as the analysis of the first segregation 21. Then, from the mapping image of Si and the mapping image of the rare earth element R obtained by the mapping analysis, a region where the segregation region of Si and the segregation region of R overlap is extracted, and the region is identified as the second segregation 22.

[0042] The average grain size of the second segregations 22 can be 2 μm or less, and is preferably 0.05 μm to 1 μm. The average grain size of the second segregations 22 may be measured in the same manner as the average grain size of the first segregations 21. That is, after identifying at least five or more second segregations 22 by the above method, the circle equivalent diameters of these second segregations 22 may be measured by image analysis to calculate the average grain size.

[0043] Similarly to the first segregations 21, the content ratio of the second segregations 22 in the ceramic layer 10 is determined by the number N2 (unit: number / μm 2 ), and this number N2 may be measured in the same manner as the number N1. In this embodiment, it is preferable to determine the content ratio of the second segregations 22 (number N2) in consideration of the content ratio of the first segregations 21 (number N1). Specifically, the ratio of N2 to N1 (N2 / N1) can be set within a range of 0.1 to 30, and preferably within a range of 0.5 to 10. By including the second segregations 22 so as to satisfy this condition, it is possible to simultaneously achieve a further improvement in durability in a high-temperature and high-humidity environment and a high relative dielectric constant.

[0044] Moreover, the second segregations 22 are preferably needle-like crystals as shown in Fig. 2, and the aspect ratio of the second segregations 22 is preferably larger than the aspect ratio of the first segregations 21. The aspect ratio of each segregation phase can be measured by image analysis of a cross section of the ceramic layer 10 as shown in Fig. 2, and can be expressed as the ratio of the maximum width in the longitudinal direction to the maximum width in the lateral direction in the segregation phase.

[0045] As described above, the ceramic layer 10 (dielectric composition) of this embodiment contains the predetermined segregation phases (21, 22), and the segregation phases can improve the durability of the multilayer ceramic capacitor 2. Note that the ceramic layer 10 may contain other segregation phases, voids, etc. in addition to the above-mentioned segregation phases (21, 22). Furthermore, the grain boundaries 23 present between the dielectric particles 20 are composed of the constituent elements of the main component and the subcomponent elements, and other segregation phases may be present in the grain boundaries 23.

[0046] Next, an example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG. 1 will be described.

[0047] First, a description will be given of the manufacturing process of the element body 4. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layers 10 after firing and an internal electrode paste that becomes the internal electrode layers 12 after firing are prepared.

[0048] The dielectric paste is manufactured using a powder of a perovskite type compound (hereinafter referred to as the main component powder) which is the main component of the dielectric composition, and a first segregation powder which becomes the first segregation 21 after firing. The main component powder can be manufactured by a solid-phase method, a hydrothermal synthesis method, an oxalate method, or the like. For example, in the solid-phase method, starting materials such as BaCO3 powder and TiO2 powder are uniformly mixed by means such as wet mixing, and then calcined to obtain a main component powder of barium titanate. At this time, the calcined main component powder may be subjected to processing such as pulverization and classification as appropriate.

[0049] The first segregation powder is obtained by mixing a compound powder containing Ba (e.g., BaCO3 powder) and a compound containing P (e.g., liquid phosphoric acid (H3PO4)) in a predetermined ratio and calcining the mixture. When preparing the first segregation powder, it is preferable to adjust the particle size of the first segregation 21 by performing a pulverization process or the like as appropriate.

[0050] In addition, when the second segregation 22 is formed in the ceramic layer 10, a second segregation powder may be prepared. This second segregation powder can be produced using a compound powder containing a rare earth element R and a compound powder containing Si, similar to the first segregation powder. In addition, the second segregation 22 may be formed by adjusting the compounding ratio of the subcomponent raw materials without preparing the second segregation powder.

[0051] The dielectric paste is obtained by adding the above-mentioned main component powder and the first segregation powder to an organic vehicle and kneading them. Here, the organic vehicle is a binder dissolved in an organic solvent. The binder to be used is not particularly limited, and may be appropriately selected from various binders such as polyvinyl butyral, acrylic, and ethyl cellulose. The organic solvent to be used is also not particularly limited, and may be appropriately selected from various organic solvents such as methyl ethyl ketone, methanol, ethanol, acetone, toluene, terpineol, and butyl carbitol.

[0052] The dielectric paste is an organic paint, but may be an aqueous paint obtained by kneading the mixed powder with an aqueous vehicle. In this case, the aqueous vehicle is prepared by dissolving a water-soluble binder, a dispersant, etc. in water. The water-soluble binder used is not particularly limited, and for example, polyvinyl alcohol, a water-soluble acrylic resin, a water-soluble polyvinyl butyral resin, etc. may be used. In this case, a second segregation powder, a subcomponent raw material, etc. are appropriately added. In addition, the dielectric paste may contain additives selected from the second segregation powder, various dispersants, plasticizers, dielectrics, subcomponent compounds, glass frit, etc., as necessary.

[0053] On the other hand, the internal electrode paste may be prepared by kneading a conductive material such as pure Ni powder or Ni alloy powder, or various oxides, organometallic compounds, resinates, etc. that will become the above-mentioned Ni or Ni alloy after main firing, together with the organic vehicle as described above. In this case, the main component powder contained in the dielectric paste may be added to the internal electrode paste as a co-material. The co-material has the effect of suppressing the sintering of the conductive powder during the firing process.

[0054] Next, the dielectric paste is formed into a sheet by a doctor blade method or the like to obtain a ceramic green sheet. Then, the internal electrode paste is applied in a predetermined pattern onto the ceramic green sheet by various printing methods such as screen printing or transfer methods. Furthermore, the green sheets on which the internal electrode patterns are formed are laminated in a plurality of layers, and then pressed in the lamination direction to obtain a mother laminate. At this time, the ceramic green sheets and the internal electrode patterns are laminated so that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the lamination direction.

[0055] The mother laminate obtained by the above process is cut into a predetermined size by dicing or pressing to obtain a plurality of green chips. The green chips may be solidified and dried to remove plasticizers, if necessary, and may be barrel-polished using a horizontal centrifugal barrel machine or the like after solidification and drying. In barrel polishing, the green chips are placed in a barrel container together with media and polishing liquid, and the barrel container is subjected to rotational motion, vibration, or the like. This barrel polishing polishes away unnecessary parts such as burrs generated during cutting, and forms rounded corners (corner R) on the green chips. After barrel polishing, the green chips are washed with a cleaning liquid such as water and dried.

[0056] Next, the green chip obtained above is subjected to a binder removal process and a firing process, and the element body 4 is obtained.

[0057] The conditions for the binder removal treatment are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layer 10 and the main component composition of the internal electrode layer 12. For example, the temperature increase rate is preferably 5 to 300°C / hour, the holding temperature is preferably 180 to 400°C, and the temperature holding time is preferably 0.5 to 24 hours. The binder removal atmosphere is air or a reducing atmosphere.

[0058] The firing conditions are not particularly limited and may be appropriately determined depending on the main component composition of the ceramic layers 10 and the main component composition of the internal electrode layers 12. For example, the holding temperature during firing is preferably 1200 to 1350°C, more preferably 1220 to 1300°C, and the holding time is preferably 0.5 to 8 hours, more preferably 1 to 3 hours. The firing atmosphere is preferably a reducing atmosphere, and the atmospheric gas may be, for example, a humidified mixed gas of N2 and H2. Furthermore, when the internal electrode layers 12 are made of a base metal such as Ni or a Ni alloy, the oxygen partial pressure in the firing atmosphere may be set to 1.0×10 -14 ~1.0×10 -10 It is preferable that the pressure is set to MPa.

[0059] After the firing process, annealing may be performed as necessary. Annealing is a process for reoxidizing the ceramic layer 10, and it is preferable to perform annealing when the firing process is performed in a reducing atmosphere. The conditions of the annealing process may be appropriately determined according to the main component composition of the ceramic layer 10, and are not particularly limited. For example, the holding temperature is preferably 950 to 1150°C, the temperature holding time is preferably 0 to 20 hours, and the temperature increase rate and temperature decrease rate are preferably 50 to 500°C / hour. In addition, it is preferable to use humidified N2 gas or the like as the atmospheric gas, and the oxygen partial pressure in the annealing atmosphere is 1.0×10 -9 ~1.0×10 -5 It is preferable that the pressure is set to MPa.

[0060] In the above-mentioned binder removal treatment, firing treatment, and annealing treatment, in order to moisten the N2 gas or mixed gas, for example, a wetter or the like may be used, and in this case, the water temperature is preferably about 5 to 75° C. Furthermore, the binder removal treatment, firing treatment, and annealing treatment may be performed consecutively or independently.

[0061] Next, a pair of external electrodes 6 are formed on the outer surface of the element body 4 obtained above. The method of forming the external electrodes 6 is not particularly limited. For example, when forming a baked electrode as the external electrode 6, a conductive paste containing glass frit may be applied to the end surface of the element body 4 by a dipping method, and then the element body 4 may be heated at a predetermined temperature. When forming a resin electrode as the external electrode 6, a conductive paste containing a thermosetting resin may be applied to the end surface of the element body 4, and then the element body 4 may be heated at a temperature at which the thermosetting resin hardens. Furthermore, after forming the baked electrode or resin electrode by the above method, sputtering, vapor deposition, electrolytic plating, or electroless plating may be performed to form the external electrode 6 having a multilayer structure.

[0062] Through the above steps, a multilayer ceramic capacitor 2 having external electrodes 6 is obtained.

[0063] (Summary of the embodiment) The multilayer ceramic capacitor 2 according to this embodiment has an element body 4 in which ceramic layers 10 made of a predetermined dielectric composition and internal electrode layers 12 are alternately laminated. The dielectric composition of the ceramic layers 10 has dielectric particles 20 mainly composed of a perovskite compound, and first segregations 21 containing at least P, Ba, and O. Furthermore, the Ba / Ti ratio (molar ratio) in the first segregations 21 is 1.20 or more.

[0064] The above-mentioned characteristics of the multilayer ceramic capacitor 2 make it difficult for the insulation resistance to decrease in a high-temperature, high-humidity environment, and improve durability against the high-temperature, high-humidity environment. The reason for the improved durability is not necessarily clear, but it is believed to be due to the first segregation 21 containing a predetermined element improving the bonding strength between the dielectric particles.

[0065] Generally, the ceramic layer made of dielectric ceramics and the internal electrode layer made of Ni have different material properties such as shrinkage rate and linear expansion coefficient, and this difference in properties causes stress inside the ceramic layer. Therefore, when a load such as an external force or thermal effect is applied to the element body, cracks are generated inside the ceramic layer, which is thought to lead to a decrease in insulation properties and durability. In the multilayer ceramic capacitor 2 of this embodiment, the first segregation 21 makes it easier for the constituent elements to diffuse between adjacent dielectric particles, and it is thought that the bonding strength between the dielectric particles is improved. In addition, even if a crack starts inside the ceramic layer 10, it is thought that the first segregation 21 can suppress the crack from progressing. As a result, the occurrence of cracks in the ceramic layer 10 can be suppressed, and the multilayer ceramic capacitor 2 of this embodiment exhibits excellent durability in a high-temperature and high-humidity environment.

[0066] In particular, by controlling the P / Si ratio, average grain size, and content rate (number N1) in the first segregation 21 within a predetermined range, durability against a high-temperature and high-humidity environment can be further improved.

[0067] Moreover, the ceramic layer 10 (dielectric composition) contains a second segregation 22 containing at least a rare earth element R (preferably Y and / or Dy), Si, and O. This second segregation 22 can increase the sintered density of the ceramic layer 10, thereby further improving durability in a high-temperature and high-humidity environment.

[0068] Although an embodiment of the present invention has been described above, the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0069] For example, in this embodiment, the multilayer ceramic capacitor 2 is exemplified as the multilayer ceramic electronic component, but the multilayer ceramic electronic component of the present invention may be, for example, a bandpass filter, a multilayer three-terminal filter, a piezoelectric element, a thermistor, a varistor, or the like.

[0070] In this embodiment, the ceramic layers 10 and the internal electrode layers 12 are laminated in the Z-axis direction, but the lamination direction may be the X-axis direction or the Y-axis direction. In this case, the external electrode 6 may be formed in accordance with the exposed surface of the internal electrode layer 12. The internal electrode layer 12 may be led out to the outer surface of the element body 4 via a through-hole electrode, in which case the through-hole electrode and the external electrode 6 are electrically connected. EXAMPLES

[0071] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0072] (Experiment 1) In Experiment 1, capacitor samples according to Examples 1 to 4 were fabricated in the following manner.

[0073] First, the main component powder, which is the raw material of the dielectric paste, and the first segregation powder were prepared. Specifically, the main component powder in Examples 1 to 5 was barium titanate powder (BaTiO3 powder) manufactured by hydrothermal synthesis. On the other hand, the first segregation powder was obtained by wet mixing starting materials such as liquid phosphoric acid (H3PO4) and BaCO3 powder at a predetermined ratio, calcining the mixture, and then pulverizing the mixture with a ball mill. In Examples 1 to 4, the starting materials for the first segregation powder were mixed at different compounding ratios, and the Ba / Ti ratio and P / Si ratio in the segregation 22 were controlled by the compounding ratio of the starting materials.

[0074] Next, the main component powder, the first segregation powder, the organic vehicle, and the subcomponent powders (Dy2O3 powder, MgCO3 powder, Al2O3 powder, MnCO3 powder, and V2O5 powder) were kneaded together to obtain a dielectric paste. At this time, the amount of the first segregation powder added to the dielectric paste was the same in Examples 1 to 4. The internal electrode paste was obtained by kneading Ni powder, barium titanate powder as a common material, and the organic vehicle.

[0075] Next, a green chip was manufactured by the sheet method using the dielectric paste and the internal electrode paste. The green chip was then subjected to binder removal, firing, and annealing to obtain an element body 4 having dimensions L0×W0×T0=2.0mm×1.25mm×1.25mm. In the obtained element body 4, the number of layers of the ceramic layers 10 sandwiched between the internal electrode layers 12 was 77, the average thickness of the ceramic layers 10 was 9.6μm, and the average thickness of the internal electrode layers 12 was 1.4μm.

[0076] Next, a baked electrode layer containing Cu, a Ni plating layer, and a Sn plating layer were formed in the order described above on the outer surface of the element body 4. Through the above steps, capacitor samples according to Examples 1 to 4 were obtained.

[0077] In Experiment 1, capacitor samples according to Comparative Examples 1 and 2 were obtained by the following procedure.

[0078] Comparative Example 1 In Comparative Example 1, a dielectric paste was prepared without using the first segregation powder. That is, the dielectric paste in Comparative Example 1 was prepared by mixing a main component powder (barium titanate powder), a subcomponent powder (the same subcomponent as in Example 1), and an organic vehicle. The other experimental conditions in Comparative Example 1 were the same as those in Example 1, and a capacitor sample according to Comparative Example 1 was obtained.

[0079] Comparative Example 2 In Comparative Example 2, a dielectric paste was obtained by mixing a main component powder (barium titanate powder), liquid phosphoric acid, a subcomponent powder (the same subcomponent as in Example 1), and an organic vehicle. That is, in Comparative Example 2, a dielectric paste was prepared using liquid phosphoric acid instead of the first segregation powder. The other experimental conditions in Comparative Example 2 were the same as those in Example 1, and a capacitor sample according to Comparative Example 2 was obtained.

[0080] The capacitor samples according to the examples and comparative examples produced in Experiment 1 were evaluated as follows.

[0081] Segregation Analysis In Experiment 1, the cross section of each capacitor sample was observed by STEM, and mapping analysis and point analysis were performed by EDX to identify the segregation phase present inside the ceramic layer 10. The measurement results for each example and comparative example are shown in Table 1. Note that in Comparative Example 1, a segregation phase containing P could not be confirmed, so the segregation result for Comparative Example 1 in Table 1 is marked with "-". Also, in Comparative Example 2 and Example 1, Si was not substantially detected in the P segregation site (specifically, Si was 1 mol % or less when the total content of elements excluding oxygen is 100 mol), so "-" is marked in the P / Si ratio column for Comparative Example 2 and Example 1.

[0082] Durability evaluation In order to evaluate the durability of the capacitor samples in a high-temperature and high-humidity environment, a pressure cooker bias test (PCBT) was performed. Specifically, the capacitor samples were subjected to a voltage of 100 V at a temperature of 121°C, humidity of 95%, and atmospheric pressure of 2.026×10 5 The samples were exposed to an environment of 100 Pa for a long time. The exposure time was 24 hours under condition 1, and 240 hours under condition 2 to evaluate durability under stricter conditions than condition 1. The insulation resistance of the capacitor samples was measured before and after PCBT, and samples whose insulation resistance after PCBT was reduced to 1 / 10 or less of the insulation resistance before the test were judged to be non-conforming (NG). The number of test samples under condition 1 was 80, and the number of test samples under condition 2 was 400, and the NG rate (number of samples that were NG / number of test samples (80 or 400)) was calculated for each example and each comparative example. The NG rate under condition 1 (24 hours of PCBT): 0 / 80 was used as the pass / fail standard for durability, and the lower the NG rate under condition 2, the better the durability was judged to be. The evaluation results of experiment 1 are shown in Table 1.

[0083] [Table 1]

[0084] As shown in Table 1, in Comparative Example 1, the first segregation 21 of the present invention was not present, and sufficient durability was not obtained. In Comparative Example 2, segregation containing P was confirmed, but the Ba / Ti ratio was less than 1.20, and sufficient durability was not obtained. On the other hand, in Examples 1 to 4 in which the first segregation 21 was present, the NG rate in the PCBT under Condition 1 was 0 / 80, and it was confirmed that the durability against a high temperature and high humidity environment was improved compared to each Comparative Example.

[0085] In particular, in Examples 3 and 5, the NG rate in the PCBT under Condition 2 was 0 / 400, and the durability was particularly good. From this result, it was found that the P / Si ratio in the first segregation 21 is preferably 2.5 or less.

[0086] (Experiment 2) In Experiment 2, the average particle size of the first segregation 21 was varied to obtain capacitor samples according to Examples 11 to 14. The average particle size of the first segregation 21 was controlled by the grinding conditions when preparing the powder for the first segregation. The other experimental conditions in Experiment 2 were the same as those in Example 1 of Experiment 1, and the same evaluations were performed as in Experiment 1. The evaluation results of Experiment 2 are shown in Table 2.

[0087] [Table 2]

[0088] From the results shown in Table 2, it was found that the average grain size of the first segregations 21 is preferably 0.05 μm or more and 0.50 μm or less.

[0089] Experiment 3 In experiment 3, the content ratio of the first segregation 21 (the number N1 of the segregation 22 contained in the unit cross section of the ceramic layer 10) was varied to produce capacitor samples according to Examples 21 to 24. In this case, the number N1 in each example was controlled by the amount of the first segregation powder added when producing the dielectric paste. The other experimental conditions in experiment 3 were the same as those in Example 1 of experiment 1.

[0090] In experiment 3, the same evaluation as in experiment 1 was performed, and the relative dielectric constant of the capacitor sample was also measured. The relative dielectric constant was calculated by measuring the capacitance using an LCR meter (Keysigt Technologies: E4981A Capacitance Meter). Specifically, in the measurement of the capacitance, the measurement temperature was set to 20°C, and a signal with a frequency of 1 kHz and an input signal level (measurement voltage) of 1 Vrms was input to the capacitor sample. The relative dielectric constant (unitless) was calculated based on the thickness of the dielectric layer, the effective electrode area, and the measured capacitance. The above measurement was performed on 10 samples for each example, and the average value was calculated. In this example, a relative dielectric constant of 2500 or more was judged to be good. The evaluation results of experiment 3 are shown in Table 3.

[0091] [Table 3]

[0092] From the results in Table 3, the content ratio of the first segregation 21 is 0.007 pieces / μm 2 In addition, in consideration of the effect of the segregation phase on the relative dielectric constant, the content ratio of the first segregation 21 is preferably 0.4 μm or more. 2 It has been found that it is preferable that:

[0093] Experiment 4 In experiment 4, the second segregation powder was added to the dielectric paste, and the dielectric paste was used to prepare capacitor samples according to Examples 31 to 38. Specifically, in Examples 31 to 34, a Dy-Si-O-based composite oxide powder was used as the second segregation powder. The composite oxide powder was produced by mixing Dy2O3 powder and SiO2 powder and calcining the mixture. In Examples 31 to 34, the amount of the second segregation powder added when producing the dielectric paste was changed, and the N2 / N1 ratio was controlled by the amount added.

[0094] In addition, in Examples 35 to 38, a Y-Si-O composite oxide powder was used as the second segregation powder. The composite oxide powder was produced by mixing Y2O3 powder and SiO2 powder and calcining the mixture. In Examples 35 to 38, the amount of the second segregation powder added when producing the dielectric paste was changed, and the N2 / N1 ratio was controlled by the amount added.

[0095] The other experimental conditions in Experiment 4 were the same as those in Example 1 of Experiment 1, and the same evaluation was performed as in Experiment 3. Here, for the PCBT in Experiment 4, evaluation was also performed under Condition 3, which is stricter than Condition 2. Specifically, for the PCBT under Condition 3, the exposure time was set to 500 hours in order to evaluate durability under conditions stricter than Condition 2. The evaluation results of Experiment 4 are shown in Table 4.

[0096] [Table 4]

[0097] From the results in Table 4, it was confirmed that durability against high temperature and high humidity environments is further improved by forming the second segregation 22 together with the first segregation in the ceramic layer 10. In particular, it was found that it is preferable to control the content ratio of the second segregation 22 so that N2 / N1 is 0.5 or more. In addition, in consideration of the effect of the segregation phase on the relative dielectric constant, it was found that it is preferable to control the content ratio of the second segregation 22 so that N2 / N1 is 10 or less. [Explanation of symbols]

[0098] 2. Multilayer ceramic capacitors 4 … Element body 4a … End face 4b…side 10 … ceramic layer 12 … Internal electrode layer 20...Dielectric particles 21 ... First segregation 22 ... Secondary segregation 23 … Grain boundary 6 … External electrode

Claims

1. A.B.O. 3 Dielectric particles containing as a main component a perovskite type compound represented by the formula: A first segregation including at least Ba, P, and O; The molar ratio of Ba to Ti in the first segregation (Ba / Ti) is 1.20 or more, Further having a second segregation containing at least Si, a rare earth element R, and O; The content ratio of the first segregation is N1 (unit: number / μm 2 ), and the content ratio of the second segregation is N2 (unit: number / μm 2 ) as A dielectric composition in which N2 / N1 is 0.5 or more and 10 or less.

2. The content ratio of the first segregation is 0.007 pieces / μm 2 Above, 0.4 pieces / μm 2 The dielectric composition according to claim 1, wherein:

3. 3. The dielectric composition according to claim 1, wherein a molar ratio of P to Si (P / Si) in the first segregation is 2.5 or more.

4. 4. The dielectric composition according to claim 1, wherein the average grain size of the first segregation is 0.05 μm or more and 0.50 μm or less.

5. 5. The dielectric composition according to claim 1, wherein the rare earth element R contained in the second segregation is Y and / or Dy.

6. 6. The dielectric composition according to claim 1, wherein the perovskite type compound is barium titanate.

7. A multilayer ceramic electronic component comprising the dielectric composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Oxide conductor paste using oxide conductor, and multilayer electronic component using the same

    JP2013012418A

  • Laminated ceramic electronic part

    JP2015046589A

  • Multilayer ceramic electronic component

    US10510490B1